Model Pembelajaran IPS di SMP Nusantara Makassar - Hasni Hasni; Ibrahim Ibrahim; Herman Herman (Seminar Nasional LP2M UNM, 2019)
The learning model should be a consideration for teachers to enrich the learning steps they will undertake. One of the ways to develop teaching variations is by utilizing learning models. In developing the variation of teaching, of course it is not arbitrary, but there is a goal to be achieved, namely increasing and maintaining students' attention to the relevance of the teaching and learning process, providing opportunities for the functioning of motivation, forming positive attitudes and encouraging students to learn. The purpose of this study was to find out the description of social studies learning models in Makassar Nusantara Middle School. The type used in this research is qualitative research because the data collected is not in the form of numbers but the data comes from observations, interviews and documentation. This study includes descriptive qualitative research that tends to use analysis with inductive reasoning patterns. The results of this research can be seen that the description of social studies learning models in Makassar Nusantara Makassar is using several learning models including STAD type cooperative learning models, Jigsaw learning models, bassed learnig problem learning models, mind mapping learning models, and discovery learning learning models.